Software process for integrated pattern oriented analysis and design (POAD) and component oriented programming (COP) on embedded real-time systems - Bau, Simba (2008)
Embedded Real-Time (ERT) systems are becoming increasingly necessary, especially in automotive industries. The complexity to manage the system is growing, where some of ERT applications need high dependability requirements. Component Based Software Engineering (CBSE) appeared to be an attractive approach in the domain of ERT system. CBSE could bring advantages to ERT system such as rapid development time, the ability to reuse existing component and ability to compose sophisticated software. Based on these perspectives, this project aims to enable and support the development of ERT systems based on Pattern-Oriented called Pattern-Oriented analysis and Design (POAD) and Component-based called PErsive COmponent Systems (PECOS), by identifying and defining the process of integrated POAD and PECOS Meta model. The advantages of defining the process are to support development of CASE for ERT and to promote software re-use.